2010
DOI: 10.1016/j.yjmcc.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyopathy-causing deletion K210 in cardiac troponin T alters phosphorylation propensity of sarcomeric proteins

Abstract: Ca2+ desensitization of myofilaments is indicated as a primary mechanism for the pathogenesis of familial dilated cardiomyopathy (DCM) associated with the deletion of lysine 210 (ΔK210) in cardiac troponin T (cTnT). ΔK210 knock-in mice closely recapitulate the clinical phenotypes documented in patients with this mutation. Considerable evidence supports the proposition that phosphorylation of cardiac sarcomeric proteins is a key modulator of function and may exacerbate the effect of the deletion. In this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
0
35
0
Order By: Relevance
“…A 210 has enhanced affinity for cTnI provides further evidence for the long-range effects of this mutation (72).…”
Section: Thin Filament Protein Phosphorylation As An Important Modifimentioning
confidence: 83%
“…A 210 has enhanced affinity for cTnI provides further evidence for the long-range effects of this mutation (72).…”
Section: Thin Filament Protein Phosphorylation As An Important Modifimentioning
confidence: 83%
“…Indeed, the deletion of lysine-210 of cTnT is associated with familial-dilated cardiomyopathy (52). Interestingly, this mutation, which decreased phosphorylation of cMyBP-C and cTnI (101), impairs PKA anchoring to cTnT (109). On the other hand, a polymorphism at amino acid 2906 of myospryn, which replaces a lysine with an asparagine, is associated with left ventricular hypertrophy in patients with hypertension (79).…”
Section: Akaps and Myofiber Contractilitymentioning
confidence: 99%
“…21). A subsequent biochemical study demonstrated that ⌬K210 caused Thr-203, located at the N terminus of the H1(T2) helix of TnT, to be more susceptible to phosphorylation by PKC-␣ when the TnT was complexed with TnI and TnC (57). These authors speculated that there might be a change in the electrostatic microenvironment near Thr-203 because of the deletion of Lys-210 (57).…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent biochemical study demonstrated that ⌬K210 caused Thr-203, located at the N terminus of the H1(T2) helix of TnT, to be more susceptible to phosphorylation by PKC-␣ when the TnT was complexed with TnI and TnC (57). These authors speculated that there might be a change in the electrostatic microenvironment near Thr-203 because of the deletion of Lys-210 (57). Taken together with our results, this suggests that the modification of the conserved residues located at the N-terminal side of the H1(T2) helix appears to have a more drastic, and possibly deteriorative, effect on the Ca 2ϩ -stimulated functions of cardiac muscle fibers, although it is yet to be delineated as to whether the N terminus of the helix is involved in interaction with another component of muscle proteins or is critical for the stability of the helix.…”
Section: Discussionmentioning
confidence: 99%